Integrated Treatment for an Injured Red Fox Kit (Vulpes vulpes): A Case Study - Hale–Mitchell, Lorrie; Rosenhagen, Nichole; Whittington, Julia (Wildlife Rehabilitation Bulletin, 2013)
Combining western veterinary medicine protocols with traditional Chinese veterinary medicine and physical therapy to treat a traumatically injured red fox kit led to a successful outcome and eventual release of the young fox.